Ideology, socialism and the everyday: forgotten lessons from the inter-war years?. Issue 3 (2nd September 2017) - Stears, Marc
Abstract: One of the great contributions of the Journal of Political Ideologies to the study of politics has been the emphasis it has given to recovering lost ideological traditions or subtraditions. With regard to the recent history of the United Kingdom, contributions to the Journal have long argued that there is far greater ideological complexity in British politics than is usually credited and that analysis of this complexity might throw up powerful arguments for contemporary political argument. In this essay, I take inspiration from that notion in order to establish whether a lost tradition of twentieth century British socialist thinking – that associated with a series of inter-war and mid-century thinkers who were sceptical of both modernism and the state – might throw new light on the failings of recent British Labour ideology, especially that associated with Ed Miliband's failed attempt to secure victory in the 2015 general election. The essay contends that the arguments of these earlier thinkers – and especially their obsession with crafting a 'socialism of the everyday' – could have provided a vital warning to Miliband's Labour, had it chosen to heed it.